PENGARUH PARTISIPASI KERJA, KOMUNIKASI, DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PADA PT. INDOMARCO ADI PRIMA – GUDANG INDUK JAKARTA, JABABEKA - Karno Karno; Reza Gustian Gunawan (Fakultas Ekonomi Universitas Borobudur, 2018)
This study aims to determine the effect of Work Participation, Communication, and Organizational Culture on Job Satisfaction, both directly and indirectly through Organizational Culture at PT. Indomarco Adi Prima - Gudang Induk Jakarta, Jababeka.The data used in this study are primary data collected through questionnaire methods and other literature studies. The population in this study were all employees of PT. Indomarco Adi Prima - Gudang Induk Jakarta, Jababeka with a sample of 116 respondents. The data analysis technique uses path analysis with the help of the SPSS 22 analysis system.The results showed that Work Participation, Communication, and Organizational Culture had an effect on Job Satisfaction. Work Participation influences Organizational Culture, Communication influences Organizational Culture. Work Partipation and Communication have an indirect effect on Job Satisfaction through Organizational Culture. Keywords: Job Participation, Communication, Organizational Culture, Job Satisfaction